Obstáculos que enfrenta la efectiva ejecución de sentencias - Pérez Infante, Liliana (2025)
Executive trials are legal procedures provided for by law with the purpose of obtaining compliance with a certain obligation that has not previously been executed in the agreed manner, which is reflected in documents whose names are executive titles, which in themselves contain a probative value. Its main objective is to ensure that the creditor, faced with the debtor's refusal to pay, can request the immediate execution of the obligation in whole or in part through the judicial process, that is, the executive trial, which begins a procedure that must be developed in accordance with all the guarantees provided for in current regulations, ensuring that no arbitrariness is committed...............